Laminar forced convection heat transfer from laterally perforated-finned heat sinks. (April 2017) - Shaeri, Mohammad Reza; Bonner, Richard
Highlights: Cooling performances of laterally perforated-finned heat sinks were investigated. The pressure drag was found to be the dominant compared with the friction drag. Laterally perforated-finned heat sinks reduce thermal resistances. Laterally perforated-finned heat sinks improve temperature uniformity. Abstract: Thermal and hydraulic performance of laterally perforated-finned heat sinks (LA-PFHSs) operating in the laminar flow regime were experimentally investigated and compared to that of the solid-finned heat sink (SFHS). Square cross sectional perforations at three different sizes were distributed equidistantly along the length of the LA-PFHSs. For each perforation size, five different porosities were tested. Locally measured thermal resistances at various locations along the heat sink were acquired. The results signify the key roles of geometrical parameters, mainly the fin pitches, on thermal-fluid characteristics of LA-PFHSs. The effects of both perforation size and porosity on overall pressure drops were also measured and presented. LA-PFHSs increased the pressure drops due to cavities formed over the perforations. The pressure drag was found to be the dominant pressure drop when compared with friction drag. However, the pressure drops became independent of the porosity beyond a threshold perforation size. Overall, LA-PFHSs are promising thermal management solutions to decrease thermal resistance and improve temperature uniformity across the heat sink base at a given pumping power, if the optimum range of porosity is obtained for a given perforation size. The results indicate that weight sensitive applications would be the most promising use for LA-PFHS. A new parameter as the mass-based thermal resistance was defined, and for the cases studied in this paper, over 45% reduction in the mass-based thermal resistance of the SFHS was achieved using LA-PFHSs with the maximum porosity.